HUKUM KEWARISAN ISLAM DI INDONESIA (Analisis Terhadap Buku II Kompilasi Hukum Islam) - Haika, Ratu (Mazahib, 2007)
The compilation of Islamic law (KHI) consists of three books: book one concerns of marriage; book two concerns of inheritance, and book three concerns of religious endowment. Unlike book one and book three which have other legislation regulating them i.e. Law No. 1/1974 of marriage, Government Regulation No. 9/1975 of marriage and Law No. 41/2004 of religious endowment, book two of the KHI have no other supporting legislation whilst articles available in the book two are very limited. Hence, there are many jurisprudential questions left by the KHI with regards of Islamic inheritance in Indonesia.